Upgrade UMKM Melalui Digitalisasi dan Multi-Channel - Antara, Made Ermawan Yoga (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
Abstract Community service is a routine activity carried out by the Student Association (HIMA) of the Management Study Program, Faculty of Economics and Business, National Education University. The main activity of Real Action for Social Activity (REAFOTY) #8 with the theme "Developing Digital Business as a Tool to Improve the Quality of SMEs" is Social Work with the first agenda, socialization of the importance of digital assets in online marketing; and second, mentoring for MSMEs in exploring online marketing guided by the entire committee. This community service activity aims to increase knowledge and broaden the insight of Gunaksa village residents about implementing online product/service marketing to realize sustainable MSMEs. Community service in Gunaksa Village has resulted in achievements, namely providing contributions in the form of knowledge transfer (knowledge sharing) regarding online marketing to Gunaksa village residents, especially MSME actors, also providing clear and explicit guidance on the steps to market products/services online to realize sustainable MSMEs.